Open Economy Macroeconomics Using Models of Closed Systems - Wynne Godley (Levy Economics Institute of Bard College, 1999)
The following paper presents a series of two-country models, each of which makes up a whole world. The models are all based on a rigorous and watertight system of stock and flow accounts and can be used to generate numerical simulations of the way in which of the whole system evolves through time on various assumptions regarding institutions, policies, and behavioral responses. The paper emphasizes that the supply of internationally traded assets is as important as demand in the determination of exchange rates. All the models describe income determination and inflation as well as international trade and intercountry dealings in assets. Apart from deploying a method of analysis believed to be capable of substantial further development, the paper finds that no vestige of the "price-specie flow" mechanism remains once asset demands and supplies are comprehensively represented and inter-related with income flows. It also finds that once the supply of internationally traded assets (for instance, as a result of imbalances in trade) are taken into account, the role of expectations in determining exchange rates–though very important–is exaggerated in much contemporary theorizing.
Keywords: 330